OS 10 ARTIGOS MAIS ACESSADOS NO ANO 2021 - Magera Conceição , Márcio; Samuel, Wilson; Ferreira Martins , Rafael; Machado, Andreia de Bem; Richter, Marc Francois; Maria da Silva, Carmem Cícera; Carvalho, Nubia Luiza Corrêa; Fonseca, Gustavo Graciano; Ferigato, Evandro; Furtado Filho, Flávio Luiz; Flach, Leonardo; Sallaberry, Jonatas Dutra; et al. (RECIMA21 - Revista Científica Multidisciplinar - ISSN 2675-6218, 2021)
Os 10 artigos mais acessados no ano de 2021 da Revista RECIMA21.